Does new public management repel talent? Findings from a choice experiment among German researchers - Torben Schubert; Henning Kroll; Maria Karaulova; Knut Blind (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
This paper analyses the factual effects of new public management governance on academics' job choice. Based on a large-scale choice experiment carried out with faculty from Germany's nine leading technical universities, we find that working environments characterised by levels of administrative burden and high expectations concerning third party funding acquisition are detrimental to self-actualisation and hence tend to repel potential candidates. More specifically, we find this effect to be most pronounced for those candidates that universities would be strategically most interested in: researchers with a strong track record and an interdisciplinary profile. Not denying potential benefits of external incentives for existing faculty, we therefore suggest to acknowledge intrinsic motivation as the key driving factor of academics choices and to design future governance structures accordingly.
Keywords: 330; Choice Experiment; German Researchers; Fraunhofer ISI